learning subject and supporting through direct instruction model to increase students’ achievement in Physical Chemistry I classL - Aceng Haetami (SAINS : Jurnal Kimia & Pendidikan Kimia, 2012)
The aim of this research is to know how materials coherent learning subject and supporting throughDirect Intruction Model (DIM) can increase students achievement in learning Physical Chemistry I.The metode used in this research is classroom action research using Direct Intruction Model (DIM).The results show that materials coherent learning subject and supporting through DIM can increase: (a)achievement in learning Physical Chemistry I increasing for every cycle: cycle I (average = 56,36) ,cycle II (average = 56,72), and cycle III (average = 61,36) ; (b) number of students complete learned(getted score ≥ 66) : cycle I (44,44 %) , cycle II (52,78 %), and cycle III (63,89 %) even complete classis not reached.